ANALYSIS OF PEDAGOGICAL COMPETENCY OF PROSPECTIVE MIDDLE SCHOOL PROFESSIONAL TEACHERS - Sinta Nurlela; Taopik Ramdan, Opi Ropiqoh, Novi Ardilah (International Journal of Teaching and Learning, 2024)
This research aims to describe: 1) students' mastery of pedagogical competencies in the scientific field of Junior High School Teacher Education Services; 2) obstacles to pedagogical competence faced by informants; 3) the efforts made by the informant to overcome obstacles to pedagogical competence. This research is qualitative research using descriptive methods. The research results show that 1) prospective teachers are able to master several competencies, so informants need to improve the implementation of educated learning; 2) the obstacles faced by informants are that they still do not master the content material well; lack of creativity in media development; and they haven't mastered classical management well; 3) the effort required by the informant is to increase knowledge about learning materials by looking for references from various sources, increasing creativity in media development, as well as being able to be firm and able to reprimand students.